2021
DOI: 10.3389/fcell.2021.658642
|View full text |Cite
|
Sign up to set email alerts
|

HNRNPA2B1 Affects the Prognosis of Esophageal Cancer by Regulating the miR-17-92 Cluster

Abstract: N6-methyladenosine (m6A) is the most abundant RNA modification in eukaryotes. Accumulating evidence suggests that dysregulation of m6A modification significantly correlates with tumorigenesis and progression. In this study, we observed an increased expression and positive correlations of all 25 m6A regulators in esophageal cancer (ESCA) data obtained from the TCGA database. Through expression profiling of these regulators, a prognostic score model containing HNRNPA2B1, ALKBH5, and HNRNPG was established, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 47 publications
(61 reference statements)
1
51
0
Order By: Relevance
“…Still other studies have found that HNRNPA2B1 can promote cell proliferation and regulate apoptosis of human colon cancer via the ERK/MAPK signaling, which indicates HNRNPA2B1 provides a potential treatment site for colon cancer (Tang et al, 2021). At the same time, also studies have found that HNRNPA2B1 was the oncogenic gene in esophageal cancer(ESCA), the increased expression of HNRNPA2B1 could predict adverse prognosis of ESCA by affecting tumor-promoting signaling pathways, silencing HNRNPA2B1 could inhibit the proliferation of ESCA cells (Li et al, 2021). Also overexpression of HNRNPA2B1 is correlated with poor survival in gastric cancer (GC), multiple myeloma (MM) and ovarian cancer and HNRNPA2B1 acts as an oncogenic role in their progression (Yang et al, 2020;Jiang et al, 2021;Peng et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Still other studies have found that HNRNPA2B1 can promote cell proliferation and regulate apoptosis of human colon cancer via the ERK/MAPK signaling, which indicates HNRNPA2B1 provides a potential treatment site for colon cancer (Tang et al, 2021). At the same time, also studies have found that HNRNPA2B1 was the oncogenic gene in esophageal cancer(ESCA), the increased expression of HNRNPA2B1 could predict adverse prognosis of ESCA by affecting tumor-promoting signaling pathways, silencing HNRNPA2B1 could inhibit the proliferation of ESCA cells (Li et al, 2021). Also overexpression of HNRNPA2B1 is correlated with poor survival in gastric cancer (GC), multiple myeloma (MM) and ovarian cancer and HNRNPA2B1 acts as an oncogenic role in their progression (Yang et al, 2020;Jiang et al, 2021;Peng et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…HNRNPC enhances the stability of ZEB1 and ZEB2 mRNA and promotes the development of esophageal squamous cell carcinoma [ 266 ]. High expression of HNRNPA2B1 has been associated with a low survival rate in esophageal cancer [ 267 ].…”
Section: M6a and Cancersmentioning
confidence: 99%
“…HnRNPA2/B1 could serve as a trigger for RNA switch to modulate the function of miRNAs or lncRNAs in cancer cells [ 90 ]. Illustratively, hnRNPA2/B1 affected the prognosis of ESCA by regulating the miR-17-92 cluster [ 91 ], facilitated the malignant phenotype of OC by activating Lin28B [ 92 ], and advanced lung cancer progression by contributing to miR-106b-5p maturation [ 88 ]. In some cases, the oncogenic roles and expression of hnRNPA2/B1 were instead impacted by certain upstream effectors.…”
Section: The Roles Of Hnrnpa/b In Cancers: Molecular Mechanisms and C...mentioning
confidence: 99%